FishDB: an integrated functional genomics database for fishes - Liandong Yang; Zetan Xu; Honghui Zeng; Ning Sun; Baosheng Wu; Cheng Wang; Jing Bo; Lin Li; Yang Dong; Shunping He (BMC Genomics, 2020)
Abstract Background Hundreds of genomes and transcriptomes of fish species have been sequenced in recent years. However, fish scholarship currently lacks a comprehensive, integrated, and up-to-date collection of fish genomic data. Results Here we present FishDB, the first database for fish multi-level omics data, available online at http://fishdb.ihb.ac.cn . The database contains 233 fish genomes, 201 fish transcriptomes, 5841 fish mitochondrial genomes, 88 fish gene sets, 16,239 miRNAs of 65 fishes, 1,330,692 piRNAs and 4852 lncRNAs of Danio rerio, 59,040 Mb untranslated regions (UTR) of 230 fishes, and 31,918 Mb coding sequences (CDS) of 230 fishes. Among these, we newly generated a total of 11 fish genomes and 53 fish transcriptomes. Conclusions This release contains over 410,721.67 Mb sequences and provides search functionality, a BLAST server, JBrowse, and PrimerServer modules.